The Effect of Work Fatigue, Work Boredom, Workload and Work Stress on Cyberloafing At Pt. The Paradise of Indonesian Motorcycles Operational Section (Planet Tire) Semarang Residency (Plat H) - Inovia Rizka Amalina; Noni Setyorini; Ira Setiawati (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2022)
This study aims to determine the effect of work fatigue, work boredom, workload and work stress on cyberloafing on employees of PT. The Paradise of Indonesian Motorcycles for Operations (Planet Tires) Semarang Residency. This study used 133 respondents, the data collection process was carried out by distributing questionnaires using google from to employees of the operational division of Planet Ban. This research is using quantitative methods. The data collection method used a saturated sampling technique with a questionnaire. This research uses multiple linear regression analysis method with statistical test tools. Measurements in this study using a Likert scale and data processing in this study using the IBM SPSS 26 tool. The results of this study indicate that there is an influence between work fatigue and work boredom on cyberloafing. Workload and work stress have no effect on cyberloafing, and work fatigue, work boredom, workload and work stress affect cyberloafing simultaneously. The results of testing the coefficient of determination obtained the value of Adjusted R Square of 0.739 or 73.9%. This means that the Cyberloafing variable can be explained by the variables of work fatigue, work boredom, workload and work stress of 73.9%, while the remaining 0.261 or 26.1% is influenced by other variables not examined in this study.